2016
DOI: 10.1002/aoc.3683
|View full text |Cite
|
Sign up to set email alerts
|

Facile green one‐pot synthesis of novel thiazolo[3,2‐a]pyrimidine derivatives using Fe3O4@l‐arginine and their biological investigation as potent antimicrobial agents

Abstract: Thiazolopyrimidine derivatives are well known because of their excellent therapeutic properties. In this investigation, an effective one‐pot three‐component method is described for the synthesis of novel 2‐[(Z)‐1‐(substituted phenyl)methylidine]‐7‐methyl‐3‐oxo‐5‐(substituted phenyl)‐2,3‐dihydro‐5H‐thiazolo[3,2‐a]pyrimidine‐6‐carboxilic acid tert‐butyl ester derivatives by condensation reaction of 3,4‐dihydropyrimidine‐2(1H)‐thiones, various aromatic aldehydes and chloroacetyl chloride under reflux conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We have developed a facile, rapid, and efficient method for synthesis of 1,3‐diaryl‐2‐azaphenalene derivatives in good to high yield via Fe 3 O 4 @ L ‐arginine as a nanocatalyst. L ‐Arginine‐coated MNPs (Fe 3 O 4 @ L ‐arginine) were prepared by chemical coprecipitation of FeCl 3 ·6H 2 O and FeCl 2 ·4H 2 O salt solutions in the presence of L ‐arginine and used for this reaction …”
Section: Introductionmentioning
confidence: 99%
“…We have developed a facile, rapid, and efficient method for synthesis of 1,3‐diaryl‐2‐azaphenalene derivatives in good to high yield via Fe 3 O 4 @ L ‐arginine as a nanocatalyst. L ‐Arginine‐coated MNPs (Fe 3 O 4 @ L ‐arginine) were prepared by chemical coprecipitation of FeCl 3 ·6H 2 O and FeCl 2 ·4H 2 O salt solutions in the presence of L ‐arginine and used for this reaction …”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that Schiff bases play an important role by serving as chelating ligands in the main groups and transition metal coordination chemistry; owing to their stability in different oxidative and reductive conditions [9]. The interaction of these donor ligands and metal ions gives complexes of different geometries and literature survey reveals that these complexes are potentially more biologically active compounds [10] such as anticancer, antifungal, antibacterial, antimalarial, anti-inflammatory, antiviral, and antipyretic properties [11][12][13][14]. It should be noted that metal chelation can tremendously influence the antimicrobial/bioactive behavior of the organic ligands; therefore, the synthesis of various transition metal complexes has been attempted in this field [15].…”
Section: Introductionmentioning
confidence: 99%
“…The chelating properties of semicarbazone are due to ONO donor sequence and possess pharmaceutical activity. Electron rich hydrazine N atom is involved in the complex formation with metal ion with interesting medical and nonmedical properties and very popular in last decade 1,2 . [ Transition complexes of Schiff base ligands has important role in inorganic, metallo-organic and biochemistry 3,4 They have diverse, chemical, optical and magnetic properties by modifying with different ligands 5-7, the interaction of these donor ligands and metal ions gives complexes of different geometries and literature survey reveals that these complexes are biologically active such as anticancer, antifungal, antibacterial, antimalarial, antiviral, antipyretic properties [8][9][10] cobalt complexes with different Schiff bases showed antibacterial and antifungal activities [11][12][13] several compounds [14][15][16][17] are known to react with the metal ions to give coloured complexes and have been employed for development for quantitative extraction and spectrophotometric determination of metals at trace levels [18][19][20] . The interaction of transition metal ions with biologically active ligands is a subject of interest.…”
Section: Introductionmentioning
confidence: 99%